Association of angiotensin‐converting enzyme gene polymorphism with schizophrenia and depressive symptom severity in a Chinese population. (19th February 2015) - Hui, Li; Wu, Jing Qin; Ye, Min Jie; Zheng, Ke; He, Jin Cai; Zhang, Xuan; Liu, Jia Hong; Tian, Hai Jia; Gong, Ben Hong; Chen, Da Chun; Lv, Meng Han; Soares, Jair C.; et al.
<x xml:space="preserve">Abstract</x> Background Depressive symptoms are frequently observed in schizophrenia patients. Angiotensin‐converting enzyme (ACE), a key enzyme of renin‐angiotensin system, can catalyze the degradation of neuropeptides and modulate dopaminergic and serotonergic neurotransmission. Previous studies have revealed the association of the ACE gene insertion/deletion polymorphism with depressive disorder and its treatment response but not with the depressive symptoms in schizophrenia. Objective The aim of this study is to examine whether this polymorphism was associated with susceptibility to schizophrenia and with its psychopathological symptoms, especially depressive symptoms in a Han Chinese population. Methods This polymorphism was genotyped in 382 chronic patients and 538 healthy controls. Psychopathology was characterised using the positive and negative syndrome scale. Results The allelic and genotypic frequencies of this polymorphism significantly differed between patients and controls (both p < 0.001). A significant difference in the positive and negative syndrome scale depressive symptom score was observed among the three genotypes (p < 0.03), with higher score in patients with insertion/insertion (I/I) than with deletion/deletion (D/D) genotypes (p < 0.05). Furthermore, there was a significant linear correlation between the number of I alleles and the depressive symptom score (p < 0.05). Conclusions The ACE gene insertion/deletion polymorphism may play a role in susceptibility to schizophrenia and also in its depressive symptom severity in a Han Chinese population. Copyright © 2015 John Wiley & Sons, Ltd.